Effects of Orlistat/Phentermine versus Phentermine on Vascular Endothelial Cell Function in Obese and Overweight Adults: A Randomized, Double-Blinded, Placebo-Controlled Trial - Kwon YJ (Dove Medical Press, 2021)
Yu-Jin Kwon,1– 3 Hyangkyu Lee,4 Chung Mo Nam,5 Hyuk-Jae Chang,6 Young-Ran Yoon,7 Hye Sun Lee,8 Ji-Won Lee1 1Department of Family Medicine, Yonsei University College of Medicine, Severance Hospital, Seoul, Republic of Korea; 2Department of Medicine, Graduate School of Yonsei University College of Medicine, Seoul, Republic of Korea; 3Department of Family Medicine, Yongin Severance Hospital, Yonsei University College of Medicine, Yongin, Republic of Korea; 4 Yonsei University College of Nursing, Mo-Im Kim Nursing Research Institute, Seoul, Republic of Korea; 5Department of Preventive Medicine, Yonsei University College of Medicine, Seoul, Republic of Korea; 6Department of Internal Medicine, Division of Cardiology, Severance Cardiovascular Hosp, Yonsei University College of Medicine, Seoul, Republic of Korea; 7Department of Molecular Medicine, School of Medicine, Kyungpook National University, Daegu, Republic of Korea; 8Biostatistics Collaboration Unit, Department of Research Affairs, Yonsei University College of Medicine, Seoul, Republic of KoreaCorrespondence: Ji-Won LeeDepartment of Family Medicine, Yonsei University College of Medicine, Gangnam Severance Hospital, 211 Eonju‐ro, Gangnam‐gu, 06273, Seoul, 135-720, Republic of KoreaTel +82 2 2019 3480Fax +82 3462 8209Email indi5645@yuhs.acBackground: In clinical practice, concomitant treatment of orlistat with phentermine is commonly used off-label. However, clinical trials have not been performed to evaluate whether their combination improves metabolic parameters and cardiovascular risk factors other than weight loss. Therefore, we aimed to compare the efficacy of concomitant administration of orlistat and phentermine versus phentermine alone on the endothelial cell function in overweight and obese adults with back pain.Methods: We conducted a 12-week, double-blinded, placebo-controlled clinical trial involving 114 patients with a body mass index of ≥ 30 (obese) or ≥ 27 (overweight) with weight-related comorbidities. We randomly assigned patients in a 1:1 ratio to receive orlistat (120mg) three times daily and phentermine (37.5mg) once daily, or a placebo three times daily and phentermine (37.5mg) once daily. Primary endpoint was changes in endothelium-dependent vasodilatation measured using ultrasound assessment of flow-mediated dilatation (FMD). Differences within groups after intervention were compared using the paired t-test or Wilcoxon signed-rank test. Differences in changes between the groups were calculated using an analysis of covariance after adjusting for each baseline value.Results: Mean weight loss during the 12-week study period was 6.1kg in the orlistat/phentermine group and in the placebo/phentermine group. Adjusted mean changes in total and non-high-density lipoprotein cholesterol were significantly greater in the orlistat/phentermine group than in the placebo/phentermine group. Adjusted mean changes in endothelium-dependent FMD were significantly greater in the orlistat/phentermine group than in the placebo/phentermine group (4.97± 0.98% vs 2.05± 0.99%, respectively; p=0.038). Changes in endothelium-independent nitroglycerin-mediated dilatation were not significantly different between the groups.Conclusion: Orlistat/phentermine significantly improved the vascular endothelial cell function compared with phentermine alone. Orlistat might have beneficial effects on the decrease of the risk of cardiovascular disease, especially in overweight and obese patients with comorbidities.Trial Registration: ClinicalTrails.gov number, NCT03675191.Keywords: obesity, orlistat, phentermine, endothelial cell function